2020
DOI: 10.3390/polym12030638
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Properties and Potential Applications of Corncob Residue Modified by Carboxymethylation

Abstract: In this study, corncob residue (CR) valorization was simply and efficiently realized via carboxymethylation, and its enhanced performance as fillers in urea-formaldehyde (UF) resin was investigated. The structures of corncob residue and carboxymethylated derivative were analyzed by nuclear magnetic resonance (NMR), Fourier-transform infrared spectroscopy (FTIR), and Raman techniques, respectively. The thermal stability, morphology, viscosity control, and adhesive strength were then investigated to evaluate its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…phase of the cellulose, so it demonstrate that the ordered structure of the cellulose has been disrupted during the carboxymethylation of the cellulose, similar to what Gao et al [47]. Mazuki et al [48] suggested that during the etherification of the cellulose with MAC the hydrogen bonds of that join the cellulose chains are cleaved.…”
Section: Xrd Analyses Of the Produced Carboxymethylcellulosessupporting
confidence: 73%
See 3 more Smart Citations
“…phase of the cellulose, so it demonstrate that the ordered structure of the cellulose has been disrupted during the carboxymethylation of the cellulose, similar to what Gao et al [47]. Mazuki et al [48] suggested that during the etherification of the cellulose with MAC the hydrogen bonds of that join the cellulose chains are cleaved.…”
Section: Xrd Analyses Of the Produced Carboxymethylcellulosessupporting
confidence: 73%
“…However, the XRD spectra of the PA-CMC and α-CMC presented a single broad band at 2θ~18 • and 2θ = 20 • , respectively, as it can be seen in Figure 1. This band is associated with the amorphous phase of the cellulose, so it demonstrate that the ordered structure of the cellulose has been disrupted during the carboxymethylation of the cellulose, similar to what Gao et al [47]. Mazuki et al [48] suggested that during the etherification of the cellulose with MAC the hydrogen bonds of that join the cellulose chains are cleaved.…”
Section: Xrd Analyses Of the Produced Carboxymethylcellulosessupporting
confidence: 70%
See 2 more Smart Citations
“…[ 103 ] Lignin has recently been employed as an adhesive alternative to fiberboard panels, combined with other biopolymers such as chitosan, and as the only bioderived element by exploiting the lignin/built‐in biopolymer's compatibility with wood fiber. [ 104 ] Lignin can improve interfacial adhesion between wood fibers and the polymer matrix when included in the fiber of particle composites. [ 24 ] As a compatibilizer, kraft lignin, a wood flour/PP composite, is used, and mechanical testing is used to study the effect of lignin levels on compatibilization.…”
Section: Recent Applications Of Lignin‐based Biocompositesmentioning
confidence: 99%